The trade growth under the EU-SADC economic partnership agreement: An empirical assessment - Maria Cipollina (Economies, 2022)
The objective of this paper is an ex-post evaluation of the European Union-Southern African Development Community Economic Partnership Agreement (EU-SADC EPA) stemming from changes in trade flows from the six members of the SADC (Botswana, Eswatini, Lesotho, Mozambique, Namibia, and South Africa) to the European Union (EU). The analysis uses detailed import and tariff data at the Harmonized System 6-digit level (HS-6) and provides estimates of the changes in the intensive and extensive margins of trade resulting from tariff reductions, as a consequence of the EU-SADC EPA initiative. The impact on the intensity of trade is estimated using a Difference-in-Differences (DID) estimation, controlling for both country and product-level trade flows. The impact on the trade of new goods (the extensive margin) before and after the agreement is evaluated through a probit analysis. The results show that the EU-SADC EPA has a positive impact on the EU's imports from the six members of the SADC, even if significant differences emerge among sectors and countries.
Keywords: 330; difference-in-differences; EU-SADC EPA; extensive margin of trade; gravity model; intensive margin of trade; probit analysis